Viagem pelas estrelas: representação de sentimento e universalidade no conto Ginga Tetsudô no Yoru, de Miyazawa Kenji - (:unkn) unknown (Universidade Federal do Amazonas, 2023)
To research on sentiment and universality was not a simple task, as both lie within the realm of subjectivity. Nonetheless, the theme has aroused interest of several scholars over the years in different areas of research worldwide. The investigation revives debate on the terms mentioned in the field of Japanese Literature research in Brazil; there are still few investigations that explore the issue of sentiment and universality in Japanese writing. In this sense, the short story Ginga Tetsudô no Yoru, by Miyazawa Kenji, permeates this dissertation, which aims to investigate manifestations of sentiment in the author's selected narrative as a characteristic of universality. The investigation highlights the publications of the short story in Portuguese, emphasizing components of the text in both the original and translated versions. It also points out the concepts of sentiment and universality, based on the view of Pierre Brunel, Claude Pichois and André-Michel Rousseau. Finally, it analyzes elements of the narrative in face of sentimental representations and the presence of the universal. The methodological process adopted for the development of this paper occurred through qualitative approach, bibliographical research and interpretive analysis of theoretical and literary texts that make up the core of the investigated subject. Therefore, the finished investigation establishes the intertwining nature of the work Ginga Tetsudô no Yoru with the concepts of sentiment and universality, without the intention of exhausting the debate, but to present it as possible within the narrative.
Journey through the stars: representation of sentiment and universality in the tale Ginga Tetsudô, by Miyazawa Kenji
Keywords: Literatura comparada; Literatura japonesa; LINGUISTICA, LETRAS E ARTES: LETRAS: LITERATURAS ESTRANGEIRAS MODERNAS; LINGUISTICA, LETRAS E ARTES: LETRAS: LITERATURA COMPARADA; Miyazawa Kenji; Ginga Tetsudô no Yoru; Sentiment in Japanese Literature; Sentimento na Literatura Japonesa; Universalidade na Literatura; Universality in Literature